2005
DOI: 10.1001/jama.293.23.2908
|View full text |Cite
|
Sign up to set email alerts
|

Routine vs Selective Invasive Strategies in Patients With Acute Coronary Syndromes

Abstract: ESPITE ADVANCES IN INVA-sive coronary procedures over the past decade, their optimal role and timing in patients with unstable angina and non-ST-segment myocardial infarction (NSTEMI) remains a challenge. 1 The question of whether to routinely refer patients with unstable angina or NSTEMI for invasive procedures, or whether to treat such patients aggressively with pharmacological interventions followed by selective referral of those with refractory or inducible ischemia, is a decision clinicians commonly face.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
243
1
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 732 publications
(265 citation statements)
references
References 41 publications
5
243
1
16
Order By: Relevance
“…In addition, group A patients had a higher risk profile and had more elevated levels of cardiac biomarkers. Two large meta-analyses including large RCTs comparing early invasive versus conservative strategies for NSTE-ACS revealed that higher-risk patients with elevated cardiac biomarker levels at baseline benefited more from routine invasive intervention, 19 with a reduction in the combined end point of MI and death seen only in patients with high-risk features, including those with elevated troponin levels. 20 Furthermore, the occurrence of postoperative MI was extremely low in the present study, occurring most in patients operated after 72 hours of NSTEMI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, group A patients had a higher risk profile and had more elevated levels of cardiac biomarkers. Two large meta-analyses including large RCTs comparing early invasive versus conservative strategies for NSTE-ACS revealed that higher-risk patients with elevated cardiac biomarker levels at baseline benefited more from routine invasive intervention, 19 with a reduction in the combined end point of MI and death seen only in patients with high-risk features, including those with elevated troponin levels. 20 Furthermore, the occurrence of postoperative MI was extremely low in the present study, occurring most in patients operated after 72 hours of NSTEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Many randomized, controlled trials 5,6 exclude elderly patients with specified comorbid conditions, which limits the generalizability of the results to patients in routine practice. 4,[7][8][9][10][11][12] There is a particular lack of data concerning the long-term adverse outcomes for these patients.…”
Section: Clinical Perspective On P 2404mentioning
confidence: 99%
“…In both cases female participants showed a deeper depressive symptomatology and experienced deeper burden. Other studies (Frias, Tuokko & Rosenberg, 2005;Mehta, 2005) also…”
Section: Discussion/conclusionmentioning
confidence: 91%